2011
DOI: 10.1186/1471-2458-11-197
|View full text |Cite
|
Sign up to set email alerts
|

Children who were vaccinated, breast fed and from low parity mothers live longer: A community based case-control study in Jimma, Ethiopia

Abstract: BackgroundImproving child survival through various health interventions has been one of the main preoccupations of public health programs in developing nations. However, efforts to understand the child death determinants and determine whether the health interventions are really contributing to the reduction of mortality were not satisfactory. The purpose of this study is to identify determinants and causes of child mortality.MethodsThe study was conducted in the town of Jimma, Ethiopia, using a case control st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
1
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 19 publications
(33 reference statements)
1
23
1
2
Order By: Relevance
“…In study done in Jimma from 2004 to 2005, higher level of wealth index was associated with a significant reduction in CM. Excess in mortality was observed in children who reside in household with a floor made of earth compared to that in a household with a floor made of cement [31]. Parental factors affected infants relatively more than the children, especially with regard to Acute Respiratory Infection (ARI) mortality.…”
Section: Standard Of Living Index Standard Of Living Index [Sli]mentioning
confidence: 97%
See 2 more Smart Citations
“…In study done in Jimma from 2004 to 2005, higher level of wealth index was associated with a significant reduction in CM. Excess in mortality was observed in children who reside in household with a floor made of earth compared to that in a household with a floor made of cement [31]. Parental factors affected infants relatively more than the children, especially with regard to Acute Respiratory Infection (ARI) mortality.…”
Section: Standard Of Living Index Standard Of Living Index [Sli]mentioning
confidence: 97%
“…Further analysis in both 2000 and 2005 EDHS confirmed that breastfeeding is the most important factor for reducing IM and death rate was lower for neonates who were put to breast immediately upon birth [29]. Children never breastfed had higher risk of dying than those who were breastfed [31]. The likelihood of death among children who were not breastfed was 6 times higher compared to their counterparts [23].…”
Section: Breastfeedingmentioning
confidence: 99%
See 1 more Smart Citation
“…29 In Ethiopia, studies led to the recommendation to educate mothers on the importance of family planning, breast feeding and immunization programs in efforts to reduce child morbidity and mortality. 30 Social support for women, especially for mothers of newborns, was also identified as an important element in shaping attitudes toward health and care of children. 31 In marginalized, extremely poor and hard to reach areas, mobilization of social support networks, combined with education and communication, were found to be effective in overcoming gender barriers and resistance to vaccination programs.…”
mentioning
confidence: 99%
“…9 Nesse cenário, o estudo dos fatores de risco para o óbito infantil possibilita identificar necessidades de saú-de de subgrupos populacionais que estão expostos a diferentes fatores de risco, compreender elementos da cadeia de eventos relacionados à determinação da MI dessa população específi-ca, além de ser essencial para subsidiar intervenções de saúde pública voltadas para a redução do risco de morte infantil. 10 Os óbitos infantis são mortes precoces e, em sua maioria, consideradas evitáveis por atuação dos serviços de saúde, entre outras ações e políticas. 3 Sendo assim, o estudo foi desenvolvido com o objetivo de analisar os determinantes da MI em municípios localizados no Vale do Jequitinhonha, Minas Gerais.…”
Section: Introductionunclassified